Portuguese Football Federation consensus statement 2020 - Abreu, Rodrigo (2021)
Publisher Copyright: © Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.